Bureaucratic or instructional leaders? An overview of portuguese school leaders’ perceptions on an autonomy and curriculum flexibility program - Cabral, Ilídia (2019)
Recent Portuguese educational policy is focused on granting schools a higher degree of autonomy with a view to the increasement of curriculum flexibility and the consequent improvement of learning among students. After a pilot experiment with around 225 schools involved in the “Project for Autonomy and Curriculum Flexibility” (PACF) in the school year of 2017/18, in the current school year (2018/19) all Portuguese schools were invited to join the Program, which enables them up to 25% curriculum flexibility. This is a big challenge for schools and school leaders, which drives them towards the adoption of increasingly instructional leadership practices, i.e. being essentially focused on curriculum and instruction. An open-ended questionnaire was applied to the universe of Portuguese school leaders who attended specific training sessions for the PACF (n=308), in order to collect their perceptions on the program’s strengths and weaknesses and suggestions for its improvement. A content analysis of a sample (n=35) of the answers given to the questionnaire reveals that the most positive aspect they point out is the possibility to get together with other school leaders and share their concerns, as well as good practices. This result shows that Portuguese schools still work very isolated from each other and that they could benefit from establishing professional learning communities that could bring an important contribution to their organizational development. On the other hand, the respondents are struggling with difficulties in motivating teachers to adopt innovative pedagogic practices and to manage the curriculum in a more integrated way. Another important obstacle to a successful implementation of the program seems to be the fact that Portuguese school leaders feel they are overloaded with paperwork and platform management, by the demand of the Ministry of Education, which forces them to be more focused on bureaucracy than on the curriculum and instruction.